Validation Analysis of HOTS-Based Multiple-Choice Questions in Islamic Religious Education at Al-Azhar High School Medan - Salim, Salim; Prasetia, Mohamad Aji; F, Muhammad Bagas; Lubis, Muhammad Arif Fadhillah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to determine the quality of multiple-choice questions based on Higher Order Thinking Skill's (HOTS) in Islamic Religious Education (PAI) Subjects for Class XI of Al-Azhar Medan High School in the 2022-2023 Academic Year. Content analysis is the technique used in this research. In this study, data analysis was conducted qualitatively. This means analyzing data from exam question documents on the subject of Islamic Religious Education, dividing the questions into categories C1 to C6, and then presenting the results of the data analysis in the form of percentages for each question category. The subject of this research is multiple-choice questions that have been made by the teacher of Islamic Religious Education class XI at SMA Al-Azhar Medan in the 2022–2023 academic year, totaling 35 questions. The data collection techniques used in this study are observation and analysis of data contained in question documents and answer keys. The results obtained from the analysis of the quality of items according to Bloom's taxonomy in the cognitive domain indicate that of the 35 multiple-choice questions found, 51.43% are in the HOTS categ multiple choice questions ory and 48.57% are included in the LOTS item category. Analysis of the quality of items in the aspect of difficulty level shows 32 questions (91.43%) in the medium category, 3 questions (8.57%) in the easy category, and 0 questions (0%) in the difficult category. Analysis of the quality of the items in the aspect of the differential power of the questions shows 31 questions amounting to (88.57%) good category, 3 questions (8.57%) very good category, and 1 question amounting to (2.86%) sufficient category.